Konsep Ma’rifatullah Menurutal-Ghazali (Suatu Kajian Tentang Implementasi Nilai-Nilai Akhlak al-Karimah) - Murni Murni (Ar-Raniry: International Journal of Islamic Studies, 2015)
The purpose of this study is to determine: (1) knowing Allah as the primary basis noble character education, (2) the method to integrate knowing Allah in nurturing students with noble character, (3) the function of knowing Allah in the formation of noble character, (4) the goal of developing knowing Allah in the improvement of noble character. This study takes the form of literature studies (library research), The findings of the study indicate: (1) knowing Allah as the primary basis of noble character education, to know Allah is the obligation of every human being, as mentioned in al-Qur’an and al-Sunnah, because by knowing Allah then people will know themselves. According to al-Ghazali, a person would not be able to achieve a degree of knowing Allah before he knows himself. Thus, the ability of human to achieve the degree of knowing Allah depends on his ability to know himself. (2) Methods for the integration of noble character in coaching students. First, the coaching. Through the coaching of this character it can be seen how the Islamic attention to the development of the soul should take precedence over physical development, because in this good soul will be born good deeds that in the next step will facilitate to produce goodness and happiness to all human life, both physically and spiritually. Second, the habituation. Al-Ghazali explains that habituation method is performed by repeating the experience in doing something that leaves good impressions in the soul. Third, exemplary. Exemplary method proposed by al-Ghazali is a series of conformity with the concept of educational methods applied by other experts, both in the past and present, and this exemplary method is always relevant and actual to date as well as highly relevant to the method of Islamic education. (3) the function of knowing God in the formation of a noble character. As the science of the most high and noble rank in comparison with the knowledge that exist in this world, then this knowing Allah presumably can be a principal focus and commitment that must be understood and considered by every human being, the results will be delivered to the happiness of man, salvation, tranquility and peace of body and soul, as well as the delights and pleasures of worship to Allah. (4) The purpose of the increase of knowing Allah in the development of noble character is as a director that will direct the orientation of the life of a Muslim.